Comparison of the performance of SAG2, GRA6, and GRA7 for serological diagnosis of Toxoplasma gondii infection in cats - Sabukunze, Serges; Gu, Haorong; Zhao, Lin; Jia, Honglin; Guo, Huanping (Frontiers in Veterinary Science, 2024)
Toxoplasmosis is an important zoonotic disease caused by Toxoplasma gondii that can infect almost all warm-blood animals worldwide, including humans. The high prevalence of T. gondii infection and its ability to cause serious harm to humans and animals, especially immunodeficient individuals makes it a key public health issue. Accurate diagnostic tools with high sensitivity are needed for controlling T. gondii infection. In the current study, we compared the performance of recombinant SAG2, GRA6 and GRA7 in ELISA for serological diagnosis of T. gondii infection in cats. We further investigated the antigenicity of recombinant dense granule protein 3 (rGRA3), rGRA5, rGRA8 and rSRS29A expressed in a plant-based, cell-free expression system for detecting antibodies in T. gondii-infected cats. In summary, our data suggest that GRA7 is more sensitive than the other two antigens for the serodiagnosis of T. gondii infection in cats and GRA3 expressed in the cell-free system is also a proming antigen in serological tests for detecting T. gondii infection in cats.